The association between benzodiazepines and influenza-like illness-related pneumonia and mortality: a survival analysis using UK Primary Care data - Nakafero, Georgina; Sanders, Robert D.; Nguyen-Van-Tam, Jonathan S.; Myles, Puja R. (Wiley, 2016)
Purpose: Bacterial superinfections, including pneumonia, are frequent complications of influenza-like illness (ILI). Clinical and laboratory evidence suggests that benzodiazepines and Z-drugs may influence susceptibility to infections and mortality. We investigated whether benzodiazepines and zopiclone modify the occurrence of ILI-related pneumonia and mortality.